Suppression of indoleamine-2,3-dioxygenase 1 expression by promoter hypermethylation in ER-positive breast cancer - Dewi, Dyah; Blanco, Saioa; Adam, Isabell; Weichenhan, Dieter; Schott, Sarah; Plass, Christoph; Platten, Michael; Gerhäuser, Clarissa; Trump, Saskia; Opitz, Christiane (OncoImmunology, 2017)
Kynurenine formation by tryptophan-catabolic indoleamine-2,3-dioxygenase 1 (IDO1) plays a key role in tumor immune evasion and inhibition of IDO1 is efficacious in preclinical models of breast cancer. As the response of breast cancer to immune checkpoint inhibitors may be limited, a better understanding of the expression of additional targetable immunomodulatory pathways is of importance. We therefore investigated the regulation of IDO1 expression in different breast cancer subtypes. We identified estrogen receptor α (ER) as a negative regulator of IDO1 expression. Serum kynurenine levels as well as tumoral IDO1 expression were lower in patients with ER-positive than ER-negative tumors and an inverse relationship between IDO1 and estrogen receptor mRNA was observed across 14 breast cancer data sets. Analysis of whole genome bisulfite sequencing, 450k, MassARRAY and pyrosequencing data revealed that the IDO1 promoter is hypermethylated in ER-positive compared with ER-negative breast cancer. Reduced induction of IDO1 was also observed in human ER-positive breast cancer cell lines. IDO1 induction was enhanced upon DNA demethylation in ER-positive but not in ER-negative cells and methylation of an IDO1 promoter construct reduced IDO1 expression, suggesting that enhanced methylation of the IDO1 promoter suppresses IDO1 in ER-positive breast cancer. The association of ER overexpression with epigenetic downregulation of IDO1 appears to be a particular feature of breast cancer as IDO1 was not suppressed by IDO1 promoter hypermethylation in the presence of high ER expression in cervical or endometrial cancer.